Aberrant lipid accumulation in the mouse visceral yolk sac resulting from maternal diabetes and obesity - Zhang, Man; Salbaum, J. Michael; Jones, Sydney; Burk, David; Kappen, Claudia (Frontiers in Cell and Developmental Biology, 2023)
Maternal diabetes and obesity in pregnancy are well-known risk factors for structural birth defects, including neural tube defects and congenital heart defects. Progeny from affected pregnancies are also predisposed to developing cardiometabolic disease in later life. Based upon in vitro embryo cultures of rat embryos, it was postulated that nutrient uptake by the yolk sac is deficient in diabetic pregnancies. In contrast, using two independent mouse models of maternal diabetes, and a high-fat diet-feeding model of maternal obesity, we observed excessive lipid accumulation at 8.5 days in the yolk sac. The numbers as well as sizes of intracellular lipid droplets were increased in yolk sacs of embryos from diabetic and obese pregnancies. Maternal metabolic disease did not affect expression of lipid transporter proteins, including ApoA1, ApoB and SR-B1, consistent with our earlier report that expression of glucose and fatty acid transporter genes was also unchanged in diabetic pregnancy-derived yolk sacs. Colocalization of lipid droplets with lysosomes was significantly reduced in the yolk sacs from diabetic and obese pregnancies compared to yolk sacs from normal pregnancies. We therefore conclude that processing of lipids is defective in pregnancies affected by maternal metabolic disease, which may lead to reduced availability of lipids to the developing embryo. The possible implications of insufficient supply of lipids -and potentially of other nutrients- to the embryos experiencing adverse pregnancy conditions are discussed.